A phase I study of anti‐inflammatory therapy with rilonacept in adolescents and adults with type 1 diabetes mellitus. Issue 4 (4th March 2018) - White, Perrin C; Adhikari, Soumya; Grishman, Ellen K; Sumpter, Kathryn M
Abstract : Background: The innate immune system may be activated around the time of diagnosis of type 1 diabetes (T1D). Components of this system, including cytokines such as interleukin‐1β (IL‐1β) represent potential therapeutic targets for disease modifying therapy. Objective: We conducted a phase 1 trial of rilonacept, an IL‐1 cytokine trap, in patients with T1D. Subjects and methods: Thirteen T1D patients (10 males) with median age (interquartile range, IQR) of 17 years (16‐18), a median (IQR) of 5 months (5‐7) since diagnosis. Rilonacept was administered subcutaneously for 26 weeks. Incidence of infections was the primary end‐point. Results: There were 85 adverse events; 13 were Grade 2, of which 9 (8 infectious) were judged "possibly related" to the drug. The mean (SD) C‐peptide on 2‐hour mixed meal tolerance tests decreased from 0.87 (0.42) to 0.59 (0.29) ng/mL ( P = .01 by paired t test) during 6 months on treatment. Hemoglobin A1c (HbA1c) increased from 6.8 (1.1) to 7.3 (1.1) ( P = .05), but there was not a significant change in daily insulin dose (0.41 ± 0.23 to 0.47 ± 0.18), or in insulin dose‐adjusted HbA1c (IDAA1c, 8.4 ± 1.8 to 9.0 ± 1.5). Subjects in "remission, " defined as HbA1c <6.5 and a total daily insulin dose <0.5 units/kg/24 h, decreased from 5 to 4. There were no significantly differentially expressed genes in peripheral blood leukocytes before and after rilonacept. Conclusions: Rilonacept treatment for 6 months is well‐tolerated in individuals with T1D of recent onset, but is unlikely to be efficacious as a single agent in preserving beta cell function.